2023
DOI: 10.3389/fpls.2023.1287677
|View full text |Cite
|
Sign up to set email alerts
|

Combination of seed priming and nutrient foliar application improved physiological attributes, grain yield, and biofortification of rainfed wheat

Layegh Moradi,
Adel Siosemardeh

Abstract: Seed priming and foliar application are two crop management practices that can increase grain yield and quality. The research aimed to assess the influence of seed priming and foliar application on rainfed wheat. Two field experiments with two seed priming rates (control and priming) and five foliar applications [control, urea (4%), silicon (4 mM), FeSO4.7H2O (0.6%), and ZnSO4.7H2O (0.4%)] at the anthesis/Z61 stage were conducted. Seeds were primed for 12 h at 25 ± 2°C, by soaking in an aerating solution [urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Due to the significant roles of Mac and Mic nutrients in mitigating the negative effects of drought stress on crop growth and production, through their involvement in various physiological and biochemical processes in plants, their foliar application could be a practical and cost-effective method to improve wheat performance under DI conditions. Previous studies have demonstrated that applying Mac and/or Mic nutrients to the leaves can improve crop growth and yield in water-deficient conditions [ 20 , 21 , 22 , 23 , 24 ]. However, most of these studies were conducted in controlled pot experiments, and there is limited research to support the use of foliar nutrient application to reduce DI in field conditions under arid climates.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the significant roles of Mac and Mic nutrients in mitigating the negative effects of drought stress on crop growth and production, through their involvement in various physiological and biochemical processes in plants, their foliar application could be a practical and cost-effective method to improve wheat performance under DI conditions. Previous studies have demonstrated that applying Mac and/or Mic nutrients to the leaves can improve crop growth and yield in water-deficient conditions [ 20 , 21 , 22 , 23 , 24 ]. However, most of these studies were conducted in controlled pot experiments, and there is limited research to support the use of foliar nutrient application to reduce DI in field conditions under arid climates.…”
Section: Introductionmentioning
confidence: 99%